Playing the Boys Game: Golf Buddies and Board Diversity - Agarwal, Sumit; Qian, Wenlan; Reeb, David M.; Sing, Tien Foo (American Economic Review, 2016)
We study the participation of women in golf, a predominately male social activity, and its influence on their likelihood of serving on a board of directors. Exploiting a novel dataset of all golfers in Singapore, we find that woman golfers enjoy a 54% higher likelihood of serving on a board relative to male golfers. A woman's probability of serving on the board in a large firm or in a predominately male industry increases by 117% to 125% when she plays golf. Joining the boy's informal network appears to facilitate women's entrance or success in the executive labor market.